Electromechanical actuator for car safety belt locking - Lind, Robert; ELIASSON, NIKLAS (My University, 2013)
The purpose was to find an electromechanical actuator that could replace today’s mechanical actuator that lock a car’s safety belt in case of an emergency. The actuator has to pass a list of requirements. Electromechanical actuators were studied and compared in order to find the best option for the assignment. Solenoids were proven to be the best option. A solenoid from Kuhnke was chosen to take into prototype testing. Most requirements were met with the prototype. The actuation speed of 5ms was not quite met however. With further improvements to the prototype an actuation speed of 5ms might be achievable. A life span test of more than 3 000 000 cycles were made without any detectable deformations of the prototype.
Keywords: Övrig elektroteknik, elektronik och fotonik; Inbäddad systemteknik; Transport; Other electrical engineering, electronics and photonics; Embedded Systems; Transport